2021
DOI: 10.1136/rmdopen-2021-001782
|View full text |Cite
|
Sign up to set email alerts
|

Trends in amyloidosis in spondyloarthritis: results from the Spanish National Inpatient Registry over a 17-year period (1999–2015)—TREND-EspA study

Abstract: ObjectiveTo assess the incidence of amyloidosis and trends therein in patients with spondyloarthritis (SpA) over a long period (17 years).MethodsAn observational retrospective population-based matched cohort study was conducted. All the admissions of patients with SpA, including ankylosing spondylitis (AS), psoriatic arthritis (PsA), arthritis associated with inflammatory bowel disease (SpA-IBD) and reactive arthritis (ReA), reported between 1999 and 2015, were analysed and a control group matched by age, sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“… 21 , 22 , 23 , 24 Interestingly, IBD shares part of similar pathogenesis of AS meanwhile it is known that around 40% of AS patients have subclinical bowel inflammation. 25 , 26 , 27 Whereas, no evidence reveals the blood CDC42 expression in AS patients. The present study exhibited that blood CDC42 expression was lower in AS patients compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 23 , 24 Interestingly, IBD shares part of similar pathogenesis of AS meanwhile it is known that around 40% of AS patients have subclinical bowel inflammation. 25 , 26 , 27 Whereas, no evidence reveals the blood CDC42 expression in AS patients. The present study exhibited that blood CDC42 expression was lower in AS patients compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted an observational, retrospective, population-based, serial cross-sectional study. This study has a similar methodology to other studies carried out by our group 18…”
Section: Methodsmentioning
confidence: 85%
“…Given that it is an observational retrospective study, a causal relationship cannot be established with the results found. Even if the MBDS provides information from a network of hospitals that covers more than 98% of the population living in Spain,18 some OS may have not been properly recorded by the public hospital discharge registry, and there may be coding errors. In addition, cases of OS in patients with SpA may not have been coded as SpA, thus implying an underestimation in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Die Amyloidose ist gemäß einer landesweit zwischen 1999 und 2015 in Spanien durchgeführten Hospitalisierungsstudie mit einer Prävalenz von im Mittel 0,7 % eine seltene Komplikation der axSpA, die zudem häufiger bei gleichzeitig vorliegender chronisch entzündlicher Darmerkrankung bzw. "inflammatory bowel disease" (IBD) gefunden wurde, v. a. aber in der Gesamtgruppe von Jahr zu Jahr im Mittel um 4,6 % abgenommen hat [16]. Insgesamt aber hatte die Amyloidose in dieser Studie als Komplikation anderer Entitäten zugenommen, sodass es keinen offensichtlicheren Grund für den rückläufigen Trend der Amyloidose bei der axSpA als den Einsatz der Biologika gibt.…”
Section: Extraspinale Manifestationenunclassified